(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2025)
This paper elaborates the precise correlation between metallic ratios and the different families of primitive Pythagorean triples. This paper also discusses the explicit formulae those provide the mathematical relationships between different metallic numbers. Main purpose of this paper is to highlight the geometric substantiation of metallic means in Pythagorean triples and other right triangles, and the trigonometric expression of the metallic ratios.